Pain in patients in critical condition and its environment - O. Carrillo-Torres; M.A. Mendiola-Roa; M.A. Ramirez-Torres (Revista Médica del Hospital General de México, 2018)
It is known that pain is the most disturbing symptom-syndrome in patients in any context of medical therapy, so the comprehensive critical care (biological–psychological–social–spiritual) approach should be adequately addressed in the patient–family–healthcare team triad when structuring major therapeutic care. Health status, as well as admission to the High Dependency Unit and/or Intensive Care Unit represents an event often accompanied by dependency, uncertainty, fear, multiple losses, vulnerability, suffering and near-death experiences. Patients in intensive care often experience multiple and recurrent acute stressors, where their response and ability to cope depend on a variety of neuropsychological, cognitive, emotional, and social functions and the support that is given to them in these areas. Resumen: Se sabe que el dolor es el síntoma-síndrome más preocupante en los pacientes en cualquier contexto de terapéutica médica, por lo que en medicina crítica el abordaje integral (biológico–psicológico–social–espiritual) debe ser adecuadamente abordado en la tríada paciente-familia-equipo de salud (ES) al ser los principales estructurantes de la atención terapéutica. El estado de salud, así como el ingreso a la Unidad de Terapia Intermedia (UTI) y/o a la Unidad Cuidados Intensivos (UCI) representa un evento acompañado frecuentemente de dependencia, incertidumbre, temor, múltiples pérdidas, vulnerabilidad, sufrimiento y experiencias cercanas a la muerte. Los pacientes en cuidados intensivos experimentan a menudo múltiples y recurrentes factores de estrés agudo, donde la respuesta y afrontamiento depende de una variedad de funciones neurofisiológicas, cognitivas, emocionales, sociales y el apoyo que se les brinde en estos aspectos. Keywords: Pain, Critically ill patients, Intensive care, Palabras clave: Dolor, Paciente crítico, Cuidados intensivos